Influence of polyoxovanadate and phthalocyanine on 4f electron transfer in gold-confined monolayers probed with EGaIn top contacts - Soni, Saurabh; Thein, Irina; Aidi, Michael; Moors, Marco; Mthembu, C. Lungani; Zharnikov, Michael; Havenith, Remco W. A.; Monakhov, Kirill Yu.; Chiechi, Ryan C. (ACS applied nano materials, 2023)
This work describes the effects of dodecavanadate anions and phthalocyanine ligands as well as the identity of lanthanide centers on the charge transport characteristics of heterometallic complexes (nBu4N)3[HV12O32Cl(LnPc)] and (nBu4N)2[HV12O32Cl(LnPc)2] for SmIII-ErIII, LuIII, and YIII on gold surfaces. In molecular ensemble junctions with eutectic Ga-In top contacts, the complexes containing two phthalocyanine ligands are highly conductive but show no clear effect of varying the lanthanide. By contrast, the complexes that omit phthalocyanine but include 4f-functionalized dodecavanadate building blocks show clear trends in conductance, rectification, and transition voltages. Density functional theory calculations show that the occupied and unoccupied frontier orbitals in the heterometallic complexes are delocalized on the phthalocyanine ligand and dodecavanadate anion, respectively, suggesting strong lanthanide-ligand electronic coupling. Near-edge X-ray absorption fine structure spectroscopy on these complexes further suggests that the phthalocyanine ligands are arranged such that their edges are in contact with the electrodes, creating tunneling transmission channels that bypass the lanthanide, effectively obviating the electronic contributions of the lanthanide centers to charge transport. These results separate the influence of the individual constituents of these metal-ligand complexes on the tunneling charge-transport properties. These results demonstrate how strongly coupled ligands such as phthalocyanine can dominate charge transport, from which we construct design rules for harnessing the properties of f-block elements in redox-active molecular heterojunctions.